2016
DOI: 10.1002/etc.3527
|View full text |Cite
|
Sign up to set email alerts
|

Monoterpenoid‐based preparations in beehives affect learning, memory, and gene expression in the bee brain

Abstract: Bees are exposed in their environment to contaminants that can weaken the colony and contribute to bee declines. Monoterpenoid-based preparations can be introduced into hives to control the parasitic mite Varroa destructor. The long-term effects of monoterpenoids are poorly investigated. Olfactory conditioning of the proboscis extension reflex (PER) has been used to evaluate the impact of stressors on cognitive functions of the honeybee such as learning and memory. The authors tested the PER to odorants on bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 45 publications
(66 reference statements)
0
7
0
Order By: Relevance
“…learning performance of bees treated with thymol and/or imidacloprid Here, we focused on thymol as a miticide because of its demonstrated effects on olfactory memory and phototaxis (Carayon et al 2014;Alayrangues et al 2016;Bonnafé et al 2017). Bees were sourced from sixteen colonies used in Colin et al (2019a).…”
Section: Experiments 2: Comparing Visualmentioning
confidence: 99%
See 2 more Smart Citations
“…learning performance of bees treated with thymol and/or imidacloprid Here, we focused on thymol as a miticide because of its demonstrated effects on olfactory memory and phototaxis (Carayon et al 2014;Alayrangues et al 2016;Bonnafé et al 2017). Bees were sourced from sixteen colonies used in Colin et al (2019a).…”
Section: Experiments 2: Comparing Visualmentioning
confidence: 99%
“…GABA is an important neurotransmitter for both mites and insects, and hence there are legitimate concerns that thymol also affects honey bees. For example, Apilife Var®, a commercial formulation of thymol, eucalyptus oil, camphor, and levomenthol, is known to impair olfactory memory and phototactic response in bees shortly after its introduction in the hive (Carayon et al 2014;Alayrangues et al 2016;Bonnafé et al 2017). In this study, we compared the effects of two miticide treatments: the Apiguard® formulation of thymol and the Apistan® formulation of tau-fluvalinate on honey bee visual learning.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, one hypothesis to explain recurrent weakening of honey bee colonies is that disoriented bees are no longer able to find their way home [12]. Thus, the effect of stressors on bee health is not limited to lethal effects but is also related to behavioral changes [13], impaired cognitive functions and sensory abilities [14,15], and physiological [16], molecular [17] and genetic changes [10]. At present, the effects of pesticides and other stressors on bee health are still poorly understood and are not evaluated by standard regulatory procedures for risk assessment [18].…”
Section: Introductionmentioning
confidence: 99%
“…Inhaled air containing a scent can reach the circulatory system but can also stimulate brain areas directly via receptors in the olfactory epithelium. Once the signals reach the olfactory cortex, release of neurotransmitters and neuropeptides takes place, which results in a marked effect on emotions [3][4][5] . Previous studies by Goto showed that visiting a small indoor garden with 20 pots of chrysanthemums for 15 minutes improved the mood of elderly subjects with dementia 6 .…”
mentioning
confidence: 99%